Analisis Produktivitas Perempuan di Kabupaten Banggai - Nurjanna Ladjin; Arianto Taliding (Jurnal Online Manajemen ELPEI, 2023)
This study aims to analyze the involvement of women in parliament, the role of women as managers, professionals, admins and technicians as well as the role of women in increasing family income in Banggai Regency in 2010 – 2020. The data analysis method used multiple linear regression with 3 predictors. The results of the study show that women's involvement in parliament and women's involvement as managers, professionals, admins and technicians have no effect on women's work productivity, meanwhile women's participation in the world of work and increasing women's access in the utilization of economic resources against household income. The role of women in politics, professional staff and sources of income can be provided by educational opportunities for women that are affordable and of good quality as well as women's empowerment in the economic field.